Tax deferral and mutual fund inflows - evidence from a quasi-natural experiment - Giuseppe Cappelletti; Giovanni Guazzarotti; Pietro Tommasino (European Central Bank (ECB), 2014)
We propose a new method to identify the impact of a change in the tax burden on mutual fund inflows, exploiting a switch from an accrual-based to a realisation-based tax regime. We use quasi-experimental data from Italy where, starting from July 2011, the tax regime for domestic mutual funds was changed from an accruals basis to a realisation basis, while the taxation of foreign funds remained on a realisation basis. We find that the reform has had a positive effect on net inflows of Italian funds (the treated group) with respect to foreign funds (the control group). The effect is both economically and statistically significant. Moreover, we find no evidence that the increase in the demand for Italian funds came at the expense of foreign funds.
Keywords: G20; G2; H2; 330; capital income taxation; mutual funds